Complex and monosomal karyotype are distinct cytogenetic entities with an adverse prognostic impact in paediatric acute myeloid leukaemia. A NOPHO‐DBH‐AML study. (8th November 2018) - Bager, Ninna; Juul‐Dam, Kristian L.; Sandahl, Julie D.; Abrahamsson, Jonas; Beverloo, Berna; de Bont, Eveline S. J. M.; Ha, Shau‐Yin; Jahnukainen, Kirsi; Jónsson, Ólafur G.; Kaspers, Gertjan L.; Kovalova, Zhanna; Lausen, Birgitte; et al.
Summary: Data on occurrence, genetic characteristics and prognostic impact of complex and monosomal karyotype (CK/MK) in children with acute myeloid leukaemia (AML) are scarce. We studied CK and MK in a large unselected cohort of childhood AML patients diagnosed and treated according to Nordic Society for Paediatric Haematology and Oncology (NOPHO)‐AML protocols 1993–2015. In total, 800 patients with de novo AML were included. CK was found in 122 (15%) and MK in 41 (5%) patients. CK and MK patients were young (median age 2·1 and 3·3 years, respectively) and frequently had FAB M7 morphology (24% and 22%, respectively). Refractory disease was more common in MK patients (15% vs. 4%) and stem cell transplantation in first complete remission was more frequent (32% vs. 19%) compared with non‐CK/non‐MK patients. CK showed no association with refractory disease but was an independent predictor of an inferior event‐free survival (EFS; hazard ratio [HR] 1·43, P  = 0·03) and overall survival (OS; HR 1·48, P  = 0·01). MK was associated with a poor EFS (HR 1·57, P  = 0·03) but did not show an inferior OS compared to non‐MK patients (HR 1·14, P  = 0·62). In a large paediatric cohort, we characterized AML with non‐recurrent abnormal karyotype and unravelled the adverse impact of CK and MK on prognosis.